Comparison of diagnostic efficacy between 99mTc-methylene diphosphate SPECT/CT and MRI for bone and joint infections: a multicenter retrospective analysis - Gao, Hao; Li, Guoquan; Fu, Congxiao; Ren, Jun; Kang, Fei; Luo, Wen; Yin, Qian; Zhou, Cheng; Li, Bo; Lu, Shuaikun; Wang, Hu; Zhang, Yong; et al. (Frontiers in Endocrinology, 2024)
There is currently no non-invasive examination that can fully determine the diagnosis of osteomyelitis. SPECT/CT tomographic fusion imaging can provide both local metabolic activity and anatomical information to determine the condition and location. This study evaluates the diagnostic efficacy of 99m Tc-MDP SPECT/CT in bone infections, compared to MRI.In this multicenter retrospective study, 363 patients with suspected bone and joint infections or osteomyelitis were included. Participants underwent 99m Tc-MDP SPECT/CT and/or MRI examinations, supplemented by pathogenic bacterial cultures and histopathological analysis.Only SPECT/CT was tested in 169 patients, and only MRI was used in 116. 78 people have implemented both inspections and have detailed information. The diagnostic sensitivity and specificity of SPECT/CT for infection were 96% and 92% respectively, with an accuracy of 96%. For MRI, these figures were 88%, 84%, and 87% respectively.